Seed Germination Response and Tolerance to Different Abiotic Stresses of Four Salsola Species Growing in an Arid Environment - Chen, Pengyou; Jiang, Li; Yang, Weikang; Wang, Lei; Wen, Zhibin (Frontiers in Plant Science, 2022)
Land degradation caused by soil salinization and wind erosion is the major obstruction for sustainable agriculture in the arid region. Salsola species have the potential to prevent land degradation. However, there are limited information about seed germination requirements and tolerance to salinity and drought for representative Salsola species. This study aimed to assess the effects of winged perianth (seed structural features) and abiotic factors (light, temperature, salinity and drought) on seed germination of these species. These Salsola species varied considerably in seed germination characteristics. Compared with naked seeds, winged seeds had lower germination percentages for S. heptapotamica S. rosacea and S. nitraria species. Darkness decreased germination percentage of winged and naked seeds of S. rosacea, however, for S. heptapotamica and S. nitraria, decreased seed germination only when the winged perianth existed. Germination of S. heptapotamica, S. rosacea and S. nitraria seeds depended on the perianth and light conditions. The naked seeds of these three species could germinate at a wide range of temperatures, especially in light. The presence of perianth, light and temperature did not significantly influence the germination of S. ruthenica seeds. When cultivating these species, it is beneficial to remove winged perianth of seeds and sow it on the soil surface when the temperature is above 5/15 °C. In addition, seed germination of Salsola displayed high tolerance to salinity and drought. Compared with winged seeds, naked seeds showed lower recovery germination under high salinity, but had the similar recovery of germination under high PEG concentration. Our study provides detailed germination information for cultivation of these four representative Salsola species in degraded saline soils of arid zone.